Decoloniality and University Management: Unveiling Knowledge in Managerial Narratives - Bizarria, Fabiana Pinto de Almeida; Tassigny, Mônica Mota; Barbosa, Flávia Lorenne Sampaio (International Journal for Innovation Education and Research, 2020)
The research analyzes critical this points on talk twenty-one managers of a Federal University, dedicated to the Cooperation International Solidarity, having as theoretical support the South Epistemologies Project, which includes the Interceptor translation ultural and ecology of knowledge, and the Academic Dependency. By means of the speeches Critical Analysis examines four themes and two developments. The themes: “Novelt ” and Symbolic Power , unfolding from the perspective of organizational identity, adhesion and participation of its members; Academic training of students and the training of employees , including the perspective of training; Integration, Mobility, Excellence and Internationalization ; Research and Circulation of Knowledge, unfolding in the configuration of Knowledge, Experiences and Knowledge. Some questions are conclusive: a set of arguments that intend the vision of science, within its Eurocentric aspect, institutionalized and reproduced in academic dependence; the affirmation of interculturality as a power, which manifests itself in the exclusion of difference; the significance that the Institution assumes and that propagates as power struggles; identity fragmentation, in the context of managerial actions; and in the “struggle” “decolonial”, which addresses the confrontation of multiple knowledge in the conformation of “other” possibilities of social life.